Natural Killer Cells At the Forefront of Modern Immunology - Zimmer, Jacques; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Natural killer (NK) cells have been at the forefront of immunology for two decades. During that time, a great amount of information about these cells has been obtained. They are important in antiinfectious and antitumoral defense and shape the adaptive immune response. In addition, they can act as immunoregulatory cells. In recent years, the therapeutic potential of NK cells in cancer immunotherapy has become increasingly evident. This book describes in detail current knowledge about NK cells and covers a broad range of NK cell-related topics, including those that are not frequently reviewed, e.g. NK cells and allergy or NK cells and skin diseases.
Natural Killer Cells: Deciphering Their Role, Diversity and Functions -- Dissecting Human NK Cell Development and Differentiation -- Diversity of KIR Genes, Alleles and Haplotypes -- NK Cell Education and CIS Interaction Between Inhibitory NK Cell Receptors and Their Ligands -- Trogocytosis and NK Cells in Mouse and Man -- Virus Interactions with NK Cell Receptors -- The Role of NK Cells in Bacterial Infections -- NK Cells and Autoimmunity -- NK Cells and Allergy -- Natural Killer Cells and Their Role in Hematopoietic Stem Cell Transplantation -- NK Cells, NKT Cells, and KIR in Solid Organ Transplantation -- NK Cells in Autoimmune and Inflammatory Diseases -- Natural Killer Cells and the Skin -- NK Cells in Oncology -- The Role of KIR in Disease -- Interactions Between NK Cells and Dendritic Cells -- Modulation of T Cell-Mediated Immune Responses by Natural Killer Cells -- Interactions Between NK Cells and Regulatory T Cells -- Interactions Between B Lymphocytes and NK Cells: An Update -- The Regulatory Natural Killer Cells -- NK Cells and Microarrays -- Natural Killer Cells in the Treatment of Human Cancer.
Keywords: Medicine; Human physiology; Immunology; Biomedicine; Immunology; Human Physiology; Biomedicine general